2022
DOI: 10.3390/cells11172677
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the NIH3T3 Fibroblast Cell Line

Abstract: The embryonic mouse fibroblast cell line NIH3T3 is widely used in life science research, including the study of cell cycle control and primary cilia. Fibroblasts are the most important cell type in connective tissue, as they produce components of the extracellular matrix and determine tissue architecture. However, they are very heterogeneous and consist of subtypes specific to their organ of residence, among others. The NIH3T3 cell line was derived from whole mouse embryos that developed to pre-birth and is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Cilia formation in IMhu-A, IMhu-M, SH-SY5Y cells was probed using ARL13B Ab, a commonly used marker of primary cilia (43). NIH-3T3 cells, a prevalent model for the study of cilia, were used as positive control (44). Abs against IFT46 and IFT56 compatible with the rabbit ANKRD55 Abs used in this study are commercially not available; therefore, we settled on use of a compatible IFT81 Ab, and we validated some key findings with a goat IFT74 Ab in combination with a rabbit IFT46 Ab ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cilia formation in IMhu-A, IMhu-M, SH-SY5Y cells was probed using ARL13B Ab, a commonly used marker of primary cilia (43). NIH-3T3 cells, a prevalent model for the study of cilia, were used as positive control (44). Abs against IFT46 and IFT56 compatible with the rabbit ANKRD55 Abs used in this study are commercially not available; therefore, we settled on use of a compatible IFT81 Ab, and we validated some key findings with a goat IFT74 Ab in combination with a rabbit IFT46 Ab ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the improved cell growth could also be attributed to the presence of boron moieties in the NTB films. The confocal image of cells on the 0.1% NTB film exhibited a “spindle-shaped” morphology, consistent with previous findings in the literature . Furthermore, there were no discernible variations in the cellular structure when compared to the control cells grown on a coverslip (Figure S12).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The confocal image of cells on the 0.1% NTB film exhibited a "spindle-shaped" morphology, consistent with previous findings in the literature. 94 Furthermore, there were no discernible variations in the cellular structure when compared to the control cells grown on a coverslip (Figure S12). Thus, from the results, it can be concluded that NTB films are biocompatible and promote cell adhesion without affecting the morphology of cells.…”
Section: Drug Loading and Release Studymentioning
confidence: 97%
“…Overall, fibroblasts and osteoblasts are two types of cells that are in direct connection with the surface of the orthopedic implants. 73–76…”
Section: Resultsmentioning
confidence: 99%